Pengaruh Sistem Presidensial Terhadap Stabilitas Politik Di Indonesia: Perspektif Sejarah Dan Kontemporer - Achmad Taufik; Abdul Bari; Syaiful Anam; Hasbullah; Ria Kasanova (CV. ULIL ALBAB CORP, 2024)
This research explores the influence of the presidential system on political stability in Indonesia, focusing on the challenges and opportunities faced in the contemporary context. In recent years, changing political dynamics and social mobilisation through digital media have influenced patterns of political participation and polarity in society. Through qualitative and quantitative analyses, this research reveals that Indonesia's presidential system, while providing strong executive power, is often hampered by issues of political polarity and party fragmentation. The findings suggest that increased public participation, particularly among youth, is key in maintaining political stability. The research also identifies recent case studies that show how public policies that are responsive to people's aspirations can strengthen government legitimacy and create consensus among different political groups. The implications of this research suggest that policy makers need to consider structural reforms in the political system to address existing challenges and facilitate broader public engagement. Thus, political stability can be maintained in the face of the complexity of dynamic social change in Indonesia.